Dynamics of HIV-1 quasispecies diversity of participants on long-term antiretroviral therapy based on intrahost single-nucleotide variations. (March 2021) - Zhang, Yuanyuan; Yin, Qianqian; Ni, Ming; Liu, Tingting; Wang, Chen; Song, Chuan; Liao, Lingjie; Xing, Hui; Jiang, Shibo; Shao, Yiming; Chen, Chen; Ma, Liying
Highlights: This study investigated the dynamics of HIV-1 diversity in participants on long-term antiretroviral therapy. Approximately 65% of HIV mutations co-occurred in plasma HIV RNA and cellular DNA. The number and frequency of intrahost single-nucleotide variations are more representative of intrahost HIV diversity. The evolutionary rate was 0.02 mutations/day/kb in participants in whom treatment failed. Abstract: Objectives: Human immunodeficiency virus (HIV) quasispecies diversity presents a large barrier to the eradication of HIV. The aim of this study was to investigate intrahost HIV quasispecies diversity and evolutionary patterns underpinning the mechanisms of viral pathogenesis during antiretroviral therapy (ART). Methods: Forty-five participants with HIV-1 infection were enrolled in a follow-up cohort for >84 months in 2004, and received a lamivudine-based first-line ART regimen. Blood samples were collected every 6 months to measure viral load and CD4 + cell count. Ultra-deep sequencing and phylogenetic analysis were used to characterize the dynamics governing quasispecies diversity of HIV-1 circulating between plasma RNA and cellular DNA of participants with treatment failure (TF, n = 20) or virologic suppression (VS, n = 25). Results: Analysis of the distribution of intrahost single-nucleotide variations (iSNVs) and their mutated allele frequencies revealed that approximately 65% of the quasispecies co-occurred in plasma HIV RNA and cellular DNA either before or after ART. The number and frequency of iSNVs are more representative of intrahost HIV diversity, and have better generalizability than phylogenetic inference by measurement of phylogenetic associations. Furthermore, drug-resistance-associated mutations (DRAMs) accumulated to high levels, dramatically increasing the DRAM-to-total-mutation ratio for TF patients. Linear regression analysis revealed that emergent mutations accumulated faster in TF patients compared with VS patients, at a rate of 0.02 mutations/day/kb. Conclusions: Based on iSNV analysis, the results demonstrate the dynamics of intrahost HIV quasispecies diversity in patients on ART, and provide a novel insight into the persistence of HIV and development of DRAMs.